Achieving sustainable, environmentally viable, solarized vaccine cold chain system and vaccination program—an effort to move towards clean and green energy-driven primary healthcare in Lebanon - Kapuria, Bhrigu; Sami Hamadeh, Randa; Mazloum, Farah; Korbane, Joe Akl; Aung, Kyaw; Kamal, Doaa; Chamoun, Nariman; Syed, Sabin (Frontiers in Health Services, 2024)
In response to Lebanon's acute economic and energy crises severely affecting healthcare, particularly vaccine storage, this study explores the transition to Solar Direct-Drive (SDD) refrigerators for vaccine preservation. Traditional gas or kerosene-powered refrigerators in Lebanon often failed to maintain the necessary temperature ranges for vaccine efficacy, prompting a shift to WHO-prequalified SDD units that operate independently of the power grid.The research adopted a multi-phase methodology, starting with an inventory assessment of existing cold chain equipment, followed by a stepwise implementation of SDD refrigerators across various health facilities, including Primary Health Care Centers (PHCCs) and dispensaries. Each phase was evaluated for feasibility, cost-effectiveness, and environmental impact. Findings indicate that solarization significantly reduces vaccine wastage by ensuring stable temperature control and cuts operational costs by decreasing dependence on non-renewable energy sources.With over 1,000 SDD units installed, vaccine storage was improved across more than 800 health facilities. Moreover, solar-powered systems in PHCCs have bolstered vaccine preservation and enhanced the resilience and sustainability of health services overall. The study concludes that solarization is critically necessary for healthcare infrastructures in similar crises. By integrating solar energy, Lebanon's vaccine cold chain system has become more reliable, cost-effective, and environmentally sustainable, thereby boosting public trust in the national immunization program. This model offers a robust framework for other regions facing analogous economic and energy challenges, underscoring the importance of renewable energy solutions in healthcare.